Meningkatkan Semangat Belajar Anak Usia Dini Melalui Penggunaan Media Gambar Pada Anak Usia 5-6 Tahun TK Yayasan Misi Islamiyah - Sulastri Sulastri; Tri Rahma Karlina Sari; Sulistiyani Sulistiyani (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study was motivated by the low enthusiasm for learning of early childhood (5-6 years) at YMI Inecda Kindergarten, Tani Makmur Village, therefore researchers tried to implement an alternative solution in the form of using image media at YMI Inecda Kindergarten, Tani Makmur Village with the aim of increasing the enthusiasm for learning of early childhood through the use of image media. The research method used is descriptive with the form of Classroom Action Research. The subjects in this study amounted to 15 children. The results of data analysis that: 1) Learning planning such as determining subject matter and formulating goals, developing and organizing learning media, 2) Learning steps include: conducting learning, carrying out assessment of the process and learning outcomes, 3) improving abilities with indicators: Coloring simple picture shapes neatly, making pictures and telling the contents of the picture with some scribbles / writings that are already in the form of letters / words, reading picture story books that have simple sentences and telling the contents of the book by pointing to some words he knows, in increasing the enthusiasm for learning in early childhood by using image media at YMI Inecda Kindergarten, Tani Makmur Village, namely children become enthusiastic about learning reaching 95%. Keywords: Enthusiasm, Picture Media, picture story books